Single chip SPR and fluorescent ELISA assay of prostate specific antigen. Issue 23 (15th October 2015) - Breault-Turcot, J.; Poirier-Richard, H.-P.; Couture, M.; Pelechacz, D.; Masson, J.-F.
Abstract : A multi-channel system combining fluidics and micropatterned plasmonic materials with wavelength interrogation surface plasmon resonance (SPR) and fluorescence detection was integrated from the combination of a small and motorized fluorescence microscope mounted on a portable 4-channel SPR instrument. Abstract : A multi-channel system combining fluidics and micropatterned plasmonic materials with wavelength interrogation surface plasmon resonance (SPR) and fluorescence detection was integrated from the combination of a small and motorized fluorescence microscope mounted on a portable 4-channel SPR instrument. The SPR and fluorescent measurements were performed based on the same detection area in a multi-channel fluidic, with a sensing scheme for prostate-specific antigen (PSA) consisting of a sandwich assay with a capture anti-PSA immobilized onto the SPR sensor and a detection anti-PSA modified with horseradish peroxidase (HRP). In this dual-detection instrument, fluorescence was measured from the solution side of the micropatterned gold film, while the interface between the glass prism and the gold film served to interrogate the SPR response. The SPR sensors were comprised of microhole arrays fabricated by photolithography to enhance the instrumental response for PSA detection by approximately a factor of 2 to 3 and they were coated with a self-assembled monolayer of a peptide (3-MPA-HHHDD-OH) to minimize nonspecific adsorption. PSA was successfully detected at clinical concentrations from 10 pM to 50 nM with this integrated system in a single assay lasting 12 minutes, almost centering on the desired range for PSA diagnostic tests (>4 ng mL −1 or >150 pM). The combination of two robust techniques in a single chip and instrument has led to a simple and effective assay that can be carried out on a small and portable instrument providing rapid biodetection of an important cancer biomarker with a dynamic range of nearly 4 orders of magnitude in the clinical range.